Primary Carcinosarcoma of Bone: A Case Report with Review of the Literature - Paczos, MD, Tamera; McGrath, MD, Brian; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2009)
Primary carcinosarcoma of the bone is an extremely rare entity with only a few other cases reported in the literature. Here we describe such a neoplasm in a 63-year-old Caucasian male who presented with back pain and a pathologic fracture of T10 with lesions at T11, T12, and L1. A CT scan was done which showed a lytic lesion in the right posterior body of T11 measuring 2.2 cm. The patient had an open biopsy of this lesion that revealed a poorly differentiated spindle cell neoplasm. Microscopically, the lesion consists of a malignant spindle cell proliferation with marked nuclear pleomorphism, nuclear hyperchromasia, and an increased N/C ratio with some multinucleated forms present. Mitotic figures and atypical mitotic figures are also noted. Immunohistochemical analysis shows that the tumor cells are positive for Vimentin, CAM 5.2, and focally positive for low-molecular weight cytokeratin and high molecular weight cytokeratin. The tumor cells are negative for S100, HMB45, melan A, SMA, muscle specific actin, desmin, pancytokeratin, EMA, CD31, CD34, CD30, Alk-1, TTF-1, calretinin, BerEP4, and thyroglobulin. The tumor cells are also negative for mucicarmine and alician blue pH 2.5. The morphology along with the immunohistochemical profile of the tumor is diagnostic for carcinosarcoma. Further workup revealed lesions in his right hip and left rib, but no other non-osteologic source for a primary lesion. The patient’s past medical history includes a resection of a scapular tumor 15 years ago that was diagnosed as low-grade chondosarcoma. These slides were reviewed and appear unrelated to the current diagnosis. The patient is currently undergoing chemotherapy with no new disease after 10 months. A literature review showed cases with similar morphologic and immunohistochemical features to this case.